Update of the WHO classification of odontogenic and maxillofacial bone tumours - Kaczmarzyk, Tomasz; Stypułkowska, Jadwiga; Tomaszewska, Romana (Journal of Stomatology, 2017)
The paper reports update of the current 2017 World Health Organization classification of odontogenic and maxillofacial bone tumours in comparison with the previous 2005 WHO classification, together with comments and presentation of the new, formerly nonclassified entities.